2013
DOI: 10.1128/mcb.01603-12
|View full text |Cite
|
Sign up to set email alerts
|

Human DEAD Box Helicase 3 Couples IκB Kinase ε to Interferon Regulatory Factor 3 Activation

Abstract: The human DEAD box protein 3 (DDX3) has been implicated in different processes contributing to gene expression. Interestingly, DDX3 is required as an essential host factor for the replication of HIV and hepatitis C virus (HCV) and is therefore considered a potential drug target. On the other hand, DDX3 interacts with IB kinase (IKK) and TANK-binding kinase 1 (TBK1) and contributes to the induction of antiviral type I interferons (IFNs). However, the molecular mechanism by which DDX3 contributes to IFN inductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
118
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(121 citation statements)
references
References 40 publications
3
118
0
Order By: Relevance
“…It is possible to speculate that after IL-17 stimulation IKKε is first recruited to CIKS and then DDX3X is recruited to the complex to regulate its biological function. To this regard, it has been recently reported that IKKε phosphorylates DDX3X and that this phosphorylation modulated the interaction between DDX3X and IRF3 (41). Therefore, it is likely that the phosphorylation of DDX3X may affect its function also in the IL-17 pathway.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible to speculate that after IL-17 stimulation IKKε is first recruited to CIKS and then DDX3X is recruited to the complex to regulate its biological function. To this regard, it has been recently reported that IKKε phosphorylates DDX3X and that this phosphorylation modulated the interaction between DDX3X and IRF3 (41). Therefore, it is likely that the phosphorylation of DDX3X may affect its function also in the IL-17 pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Not surprisingly, DDX3X was found to promote genome replication of many RNA viruses (33). However, DDX3X binds TBK1/IKK, which stimulate both IRF3 activation and interferon type I production, thereby promoting an antiviral state (10,11). This implies that DDX3X has dual functions that can either facilitate or hamper viruses.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, DDX3X also contributes to innate immunity against these viruses. For instance, DDX3X stimulates interferon (IFN) type I production by binding IKK (IB kinase epsilon) and TBK1 (tank-binding kinase 1), leading to IRF3 phosphorylation and activation (10,11). These findings position DDX3X as a critical player for the replication and immunity against RNA-based viruses.…”
mentioning
confidence: 95%
“…Notably, many of these molecules regulate RLR signaling, and also have other functions in RNA metabolism and gene transcription. DEAD-box protein 3 (DDX3) was first proposed to function as vRNA receptor, activating MAVS-dependent signaling and IFN induction [39]; however recent research indicates that DDX3 exerts a regulatory role in innate signaling by augmenting the activation of TBK1 or IKKε via direct interaction [40]. Moreover, it has been recently reported that DDX3 functions as an antiviral effector protein that restricts HBV transcription [41].…”
Section: Cytosolic Sensing Of Vrnamentioning
confidence: 99%